Mapeamento dos compartimentos de relevo do município de Estrela do Norte-SP e adjacências - Felipe, Mayara Cristina de Paula [UNESP] (2015)
The Geomorphology is to study the relevant object, which is the substrate where there are social relations, where society draws the natural resources for their survival and structure its immediate surroundings. In this context, the geomorphological map is currently considered as an important tool in landscape research. The landscapes of the city of Estrela do Norte-SP and surroundings consist mostly of geological substratum of sedimentary rock formations of Adamantina and Santo Anastácio (IPT, 1981a). Geomorphologically dominated by large reliefs of gently rolling hills tops and pedologicamente, the Oxisols and Ultisols Red-Yellow (Oliveira et al., 1999), which historically without proper management, formed a serious degradation of erosive framework in the study area. Thus, this study aimed to produce a map of the major compartments of the municipality Estrela do Norte-SP and surrounding areas, using techniques of digital stereoscopy. In relation to the procedures used in developing the mapping of geomorphological compartments, the main references were Tricart (1965) and Ross (1992). To prepare the mapping applied to refund technique - 3D through the ALOS / PRISM images...